Use of iron mine tailing as fillers to polyethylene - Coura, Ítalo R. (Sci Rep, 2021)
The iron mine tailings accumulation in dams is an environmental and economic problem. The composite based on high-density polyethylene/iron mine tailing production for the application of wood plastic and some items of domestic plastic industry can be a good alternative to reduce the rejects in the environment. This work presents the influence of the processing methodology in the mechanical, thermal and morphological properties of composites based on the high-density polyethylene/iron mine tailing. Four methodology processing by continuous and/or batch mixing were available. The iron mine tailing particles in the polymer matrix promoted an increase in mechanical strength and thermal stability. Besides, the particles acted as flame retardant. The iron mine tailing materials produced using batch mixing showed more significant modifications in the properties due to the better dispersion of the filler as shown by scanning electron microscopy.